Proposed Islamic ethics for food processing - Amanullah, Muhammad (2015)
Processed food is widespread phenomenon all over the world. Some of these foods are ready to be eaten immediately after purchasing, while others need to be cooked before eating them. In order to make higher profits, companies and suppliers of these foods sometimes do not follow the proper production methods, or use unhealthy ingredients, or do not label products correctly. This negligence causes various types of health problems in consumers. To some extent, this negligence can cause human casualties. Islam offers a number of ethics to be followed in food processing. By analyzing the related verses of the Qur’an and ahadith of the Prophet (p. b. u. h.), this paper intends to discuss these ethics. The paper may conclude that Islam has a comprehensive code of ethics for food processing. Implementation of these ethics may help reducing health problems and drawbacks that are caused by neglecting them during food processing.